Tribological investigations of the glass-to-metal contact during glass forming at an industrial scale - Orzol, Dominik Karl; Roos, Christian; Wondraczek, Lothar (International Journal of Applied Glass Science, 2021)
An industrial-scale dynamic friction test set-up was installed and optimized at the gob-stage of a prototype container glass forming line. The set-up was used to generate a fundamental understanding of the tribological interactions during container forming, considering the real-size glass gob in the viscoelastic range and the respective contact material. The findings are universally applicable for other glass-forming situations such as spinning, pressing, and blowing, where similar hot contact situations occur. The measured friction loss within that tribological system is correlated to different material properties. In doing so, existing knowledge is further developed, leading to new insights into the matter of glass-metal interactions. With that a better fundamental understanding of the process at an industry level is obtained.
CRIS-Team Scopus Importer:2023-04-20
Keywords: friction; glass forming; tribology